Boosting moisture induced electricity generation from graphene oxide through engineering oxygen-based functional groups. (April 2022) - Zhu, Renbo; Zhu, Yanzhe; Chen, Fandi; Patterson, Robert; Zhou, Yingze; Wan, Tao; Hu, Long; Wu, Tom; Joshi, Rakesh; Li, Mengyao; Cazorla, Claudio; Lu, Yuerui; et al.
Abstract: Harvesting energy from ubiquitous moisture is attracting growing interest for directly powering electronic devices. However, it is still challenging to fabricate high-performing moisture-electric generators (MEGs) with high and stable electric output. Herein, we report a simple strategy to modify the oxygen-based groups of graphene oxide using hydrochloric acid treatment, which boosts the electric output based on the device structure of graphene oxide/polyvinyl alcohol (GO/PVA) MEGs. The resulting MEG enables a stable voltage of 0.85 V and a current of 9.28 μA (92.8 μA∙cm -2 ), which are among the highest values reported so far. More excitingly, electric output gets further improved by simply assembling four MEG units in series or parallel. Moreover, the MEG shows great commercial potential for flexible and wearable applications. Driven by these advancements, the assembled MEGs can successfully power sensors and calculators. This work opens a new era of advance for a new energy conversion technology able to directly powering electronic devices. Graphical Abstract: Schematic illustration of graphene oxide-based MEG powering electronic devices ga1 Highlights: Acidification is a facile and effective way to tune the functional group density of GO materials. MEGs achieve one of the highest continuous electrical outputs with a voltage of 0.85 V and current density of 92.8 μA∙cm -2 . The density of CO bonds significantly affects the output, providing a guideline to select the target materials. A commercial pressure sensor and digital calculator can be directly powered by a single MEG and MEG array, respectively.